Condição de saúde bucal e determinantes da necessidade de prótese dentária entre idosos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present thesis aimed to analyze the oral health status of institutionalizedand non-institutionalized elderly people, exploring the association with individualfactors. Therefore we carried out two studies: a) a serial cross-sectional study, with secondary data obtained in three waves (2006, 2010 and 2015) from the Health, Well-being and Aging Study (SABE) in the Faculty of Public Health ofthe University of São Paulo (FSP/USP) and b) a cross-sectional study with primary data obtained from three Long Stay Institutions for the Elderly (LSIE) in the city of Ponta Grossa (Paraná). For both studies, the information about sociodemographic characteristics, cognitive function, general health status and clinical examination of oral health were collected using a structured questionnaire. Regarding the oral examination we used data about the rate of decayed, missing and filled permanent teeth (DMF-D), the use and the need for dental prostheses and the presence of oral lesions. Absolute and relative frequencies were obtained, as well as bivariate, multivariate and inequality regression analyzes using complex measures. The results for the first study showed that the prevalence of the need for prosthesis was 46.00%, 53.32% and63.90%, in 2006, in 2010 and in 2015, respectively. The require was greater among men, brown and black people, lower education elderly people, people with insufficient income and health insurance, people with poor self-perceptionof oral health, among those who do not use dental prosthesis and who needed urgent dental care. Relative and absolute socioeconomic inequalities were found in the three years of SABE study. Elderly people with lower education, that is, from the lowest socioeconomic group, had a higher prevalence of the need for dental prosthesis, and this inequality persisted in 2006 and in 2015.Concerning the elderly people from the LSIE, we evaluated 130individuals and, most of them aged over 80 years (60.77%). The mean DMFT-D was 30.62 (standard deviation 2.85), 62.31% of the elderly were edentulous, 41.54% used dental prosthesis whereas 79.23% needed dental prosthesis. Orallesions were identified in 35.42% of those evaluated patients and 61.29% of the elderly people classified their self- perception about oral health as good. Most of the evaluated elderly people were edentulous, they needed dental prosthesis and the self-perceived oral health as adequate. The edentulism was more prevalent among people aged eighty years or older, among those who hadbeen gone to the dentist three years ago or more, and the more teeth present in the oral cavity the worse their condition were (the more decayed component of the DMFT index). The greatest need for dental prosthesis was of the total type. We concluded that the oral condition of the elderly people in São Paulo/SP city and institutionalized people in Ponta Grossa/PR was considered poor, from the clinical point of view due to the high prevalence of edentulism and the need of the use of dental prosthesis. Persistent social inequalities were found over the years in the SABE study.
Keywords: Prótese dentária; idosos; saúde bucal; Dental Prosthesis; aged; oral health; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA